2019
DOI: 10.1007/s13201-019-1105-7
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of cost-effective AC/CeO2 nanocomposites for the degradation of selected industrial dyes

Abstract: With an increasing global usage of dyes and colorants in various industries, the increase in dye contamination level in water has frequently reported. Developments of appropriate techniques for the degradation of dyes in industrial wastewater are critical and urgently required. Utilization of low-cost materials for the treatment of various dyes using an alternative driving energy could be promising in near future. In the study, activated carbon (AC) was prepared using agricultural waste (coconut shell) and uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…This is attributed to their high selectivity, efficient active sites, high surface area to mass ratio, high adsorption capacity and catalytic activity 41 , 42 . However, due to the difficulty in separating the metallic nanoparticles from solution, instead the impregnation of these nanoparticles onto suitable adsorbent substrate to form hybrid materials has gained significant attention recently 43 , 44 . This impregnation of metallic nanoparticles onto adsorbents has been found to enhance the trapping of contaminants from water 45 , 46 .…”
Section: Introductionmentioning
confidence: 99%
“…This is attributed to their high selectivity, efficient active sites, high surface area to mass ratio, high adsorption capacity and catalytic activity 41 , 42 . However, due to the difficulty in separating the metallic nanoparticles from solution, instead the impregnation of these nanoparticles onto suitable adsorbent substrate to form hybrid materials has gained significant attention recently 43 , 44 . This impregnation of metallic nanoparticles onto adsorbents has been found to enhance the trapping of contaminants from water 45 , 46 .…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the absorption bands due to C–O stretching appeared at ν = 1167, and 1106 cm −1 as cited by Aghazadeh and Nikpassand 81 . Besides, the absorption bands at ν = 1031 (strong S=O stretching) 82 , 880 (strong C–H binding “1,2,4-trisubstituted”), 778 (strong C–H binding “1,2,3-trisubstituted”), 731 (strong C–H binding “1,2-disubstituted”) 83 , 669 (strong C–halogen “halogen = Cl, Br or I” “halogenated compound”) 84 , 605 (phosphate) 85 , 532 and 456 (two bi-phenyl rings “conjugated”) 86 .…”
Section: Resultsmentioning
confidence: 99%